2019
DOI: 10.3390/molecules25010166
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin-Based Antimicrobial Films Incorporating Pomegranate (Punica granatum L.) Seed Juice by-Product

Abstract: Pomegranate (Punica granatum L.) seed juice by-product (PSP) was added as reinforcing and antimicrobial agent to fish gelatin (FG) films as a promising eco-friendly active material for food packaging applications. A complete linkage analysis of polysaccharides in PSP showed xylan and cellulose as main components. This residue showed also high total phenolic content and antioxidant activity. Three formulations were processed by adding PSP to FG (0, 10, 30 wt. %) by the casting technique, showing films with 10 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 61 publications
1
26
0
Order By: Relevance
“…The ATR-FTIR spectra of OE (2 ± 0.01 mg) were registered, in triplicate, in the absorbance mode (4000-600 cm −1 ) using a Bruker Analitik IFS 66 FTIR spectrometer (Ettlingen, Germany) as it was described by Valdés et al [49].…”
Section: Attenuated Total Reflectance-fourier Transform Infrared Specmentioning
confidence: 99%
See 1 more Smart Citation
“…The ATR-FTIR spectra of OE (2 ± 0.01 mg) were registered, in triplicate, in the absorbance mode (4000-600 cm −1 ) using a Bruker Analitik IFS 66 FTIR spectrometer (Ettlingen, Germany) as it was described by Valdés et al [49].…”
Section: Attenuated Total Reflectance-fourier Transform Infrared Specmentioning
confidence: 99%
“…The oxygen transmission rate (OTR) was determined by following the procedure already described by Valdés et al [49] with an oxygen permeation analyzer (8500 model Systech Instruments, Metrotec S.A., Spain). Results were expressed as oxygen transmission rate per film thickness (OTR*e).…”
Section: Barrier Propertiesmentioning
confidence: 99%
“…Pomegranate (Punica granatum L.) fruit has been reported to exert a promising preventive activity against several inflammatory and chronic diseases. The main composition of pomegranate by-products as well as their potential to enhance specific functionalities in food applications has recently been reviewed by [22][23][24] who added pomegranate seed juice by-product (PSP) as reinforcing and antimicrobial agent to fish gelatin (FG) films as a promising eco-friendly active material for food packaging applications. Also, [25] stated that pomegranate has antifungal, insecticidal, antibacterial, anticoccidial, and molluscicidal effect against both plant and human pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…The FTIR analysis by Zhang et al revealed that the increasing intensity of absorption peak at 1659 cm −1 suggested that glutaraldehyde as a cross-linker could react with the amide group on chitosan/gelatin scaffolds and form a stable complex [ 30 ]. The extracts of PA and CA loaded in the GC patches encouraged the interaction of phenolic compounds with NH2 and hydroxyl groups in gelatin, which thus led to the crosslinking of the gelatin matrix [ 31 , 32 ]. It was also proved that the addition of CA extract could form hydrogen bonds with related functional groups of gelatin.…”
Section: Discussionmentioning
confidence: 99%